Asunaprevir, a protease inhibitor for the treatment of hepatitis C infection - Gentile I; Buonomo AR; Zappulo E; Minei G; Morisco F; Borrelli F; Coppola N; Borgia G (Dove Medical Press, 2014)
Ivan Gentile,1 Antonio Riccardo Buonomo,1 Emanuela Zappulo,1 Giuseppina Minei,1 Filomena Morisco,2 Francesco Borrelli,1 Nicola Coppola,3 Guglielmo Borgia1 1Section of Infectious Diseases, 2Section of Gastroenterology, Department of Clinical Medicine and Surgery, University of Naples Federico II, 3Section of Infectious Diseases, Department of Mental Health and Public Medicine, Second University of Naples, Naples, Italy Abstract: According to the World Health Organization, approximately 150 million people worldwide are chronic carriers of hepatitis C virus (HCV). HCV infection can evolve into cirrhosis of the liver and its complications, which are ultimately responsible for more than 350,000 deaths every year. Antiviral therapy, when successful, is able to decrease the rate of progression and increase survival. Two types of therapies are currently available, ie, interferon-based therapies and interferon-free ones. The latter have several advantages in terms of safety and tolerability, and could be used even in the most advanced stages of the disease. However, their use is restricted to some viral genotypes (genotype 2 and 3) and they are expensive. Several molecules are in an advanced phase of development. This review deals with the pharmacokinetics, pharmacodynamics, tolerability, and safety of asunaprevir, an inhibitor of HCV nonstructural 3 protease. Asunaprevir exerts optimal in vitro activity particularly against HCV genotypes 1 and 4, and its pharmacokinetic profile enables twice daily administration. The drawback of asunaprevir, and of all protease inhibitors, is its low barrier to resistance. Consequently, it is used in association with other drugs to prevent resistance. Specifically, when combined with daclatasvir, an NS5A inhibitor, asunaprevir results in a very high rate of viral eradication in both treatment-naïve and treatment-experienced patients, with a sustained virological response rate of 80%–90%. Tolerability is fair; in fact, asunaprevir is associated with a transient increase in aminotransferase levels, which is mild in most cases. In conclusion, asunaprevir is a good candidate component of interferon-free combinations and may revolutionize the treatment of chronic HCV infection in the near future. Keywords: NS3, interferon, ribavirin, interferon-free, daclatasvir, sofosbuvir